A cross sectional study on the prevalence and risk factors of fall among the elderly in an urban area of Chidambaram - Sindhubala, B.; Annie, I. K.; Felix, A. John William (International Journal Of Community Medicine And Public Health, 2020)
Background: In India, the elderly people constitute 8.6% of the total population. Fall is a major cause of injuries and can increase the risk of early mortality among elderly. The objective of this study was to determine the prevalence of falls among elderly and its associated risk factors. Methods: A cross sectional study was conducted among elderly population over 60 years and above, in an urban area. About 115 elderly were selected using convenient sampling method. A predesigned semi structured questionnaire was administered to collect information about falls. In statistical analysis, descriptive statistics and chi square test was employed using SPSS version 21.3. Results: The prevalence of fall in the past 12 months was found to be 27%. Among these, 77.4% of the participants had single fall and 22.6% had two episodes of falls. The majority (84.2%) of falls occurred indoors, 60.5% falls occurred during morning hours. Half of the participants had reported the reasons for falls as slippery floor (55.6%). Age was found to be significantly associated with falls. Conclusions: Falls are very common among elderly. Identification of factors significantly affecting elderly falls can help in planning public health policies and programs for prevention of falls.